Housekeeping for prefix coding. - Turpin, A. (IEEE Transactions on communications)
We consider the problem of constructing and transmitting the prelude for Huffman (1952) coding. With careful organization of the required operations and an appropriate representation for the prelude, it is possible to make semistatic coding efficient even when S, the size of the source alphabet, is of the same magnitude as m, the length of the message being coded. The proposed structures are of direct relevance in applications that mimic one-pass operation through the use of semistatic compression on a block-by-block basis